THE EFFECT OF ELECTRONIC WORD OF MOUTH ON PURCHASE DECISION ON HILAL HERBAL - Rissa Meldani Putri, - (2022)
This study was conducted to determine the effect of electronic word of mouth on consumer purchasing decisions Hilal Herbal. The object of this research is the consumer of Hilal Herbal. This study uses two variables to test the effect, namely the independent variable in this study is E-Word of Mouth (X) and the dependent variable is Purchase Decision (Y). The method used is a quantitative approach with 171 respondents. To find out the results of the research, the research method was carried out by testing data quality, testing classical assumptions, and testing hypotheses. In hypothesis testing, the results of partial statistical tests between e-word of mouth on purchasing decisions show that the value of the e-word of mouth variable of 18.959 is found to be greater than ttable 0.148 and a significance level of 0.000 <0.05 indicating that the e-word variable of mouth has a significant effect on purchasing decisions on Hilal Herbal products. Based on the coefficient of determination (R〗^2), there is an R Square value of 0.680. These results indicate the ability of the EWOM variable in explaining the purchasing decision variable, which is 0.680 or 68% which indicates that the influence of e-word of mouth (X) can influence purchasing decisions (Y). Based on the research results, companies can use e-word of mouth as a marketing tool in giving a good and positive impression or message from the product because ewom is an effective marketing tool for Hilal Herbal to market their products.